Developing Future-Ready University Graduates: Nurturing Wellbeing and Life Skills as Well as Academic Talent - Gan, Tzyy Yang; Beevi, Zuhrah; Low, Jasmine; Lee, Peter J.; Hall, Deborah Ann (Frontiers in Psychology, 2022)
Higher education is starting to embrace its role in promoting student wellbeing and life skills, especially given the concerning levels of poor mental health and uncertainties in the future job market. Yet, many of the published studies evaluating positive educational teaching methods thus far are limited to interventions delivered to small student cohorts and/or imbedded within elective wellbeing courses, and are focussed on developed Western countries. This study addressed this gap by investigating the effectiveness of an institution-wide compulsory course informed by the principles of Seligman’s Wellbeing Theory. The course was delivered at a British university in a developing country in Southeast Asia. It purposefully sought to nurture growth-oriented outcomes (including self-awareness, positive emotions, and personal effectiveness) and was taken by an entire cohort of year one undergraduate students. We tested the effectiveness of the curriculum content and staff coaching style in achieving life skills, and evaluated how these perceptions influenced students’ subjective wellbeing. A convergent mixed-methods design was used with 350 survey respondents and 11 interviewees. Perceived life skills scores showed a 2.5% improvement at the end of the course. Partial Least Squares Structural Equation Modelling tested the predicted relationships between variables. All relationships were statistically significant, but the influence of course design and educators’ style on life skills acquisition (50.8% of the variance) was moderate, while the effect on subjective happiness and life satisfaction (4–5% of the variance) was very weak. Qualitative data indicated that while quantifiable benefits to wellbeing might not be immediate, students did anticipate longer-term benefits for happiness and life satisfaction. This finding suggests that such a novel educational approach is well-received by Asian students and may sow the seeds for future benefit by positively impacting on their skills, behaviours, attitudes, and values. To achieve optimal flourishing at university, we recommend exploring teaching practises that combine positive education with coaching psychology practises.